D.E.M. modeling of biocemented sand: Influence of the cohesive contact surface area distribution and the percentage of cohesive contacts. (September 2022) - Sarkis, Marilyn; Abbas, Mohammad; Naillon, Antoine; Emeriault, Fabrice; Geindreau, Christian; Esnault-Filet, Annette
Abstract: Microbially induced calcite precipitation (MICP) is a recent technique used to reinforce the soil. In the present work, a 3D Discrete Element Method (DEM) model for biocemented sand is set up. It takes into account real contact properties, such as the cohesive contact surface area distribution and the percentage of cemented bonds, which have been computed from 3D synchrotron X-ray images at high resolution of biocemented sand with different amounts of calcite, ranging from 0 to 14.9% in volume (i.e. 19.6% in mass). Triaxial tests under different confining pressures are simulated. The macroscopic response of numerical and physical specimens are compared. Overall, these simulations show that the above contact properties play an important role on the macroscopic response and the proposed numerical model allows to describe with a good accuracy the macroscopic responses of lightly cemented samples (below 4% in volume), whereas it requires future developments to well represent the behavior of medium and highly cemented samples.